Pathway for Implementation of Hereditary Breast Cancer Screening - Datar, Sneha Rajan (Digital Repository of Theses, 2026)
Hereditary breast cancer, by and large associated with genetic mutations usually inherited, like BRCA1 and BRCA2, is an emerging yet poorly met challenge within the Indian healthcare system. With advances in genetic testing and preventive oncology, the implementation of hereditary breast cancer screening continues to remain fragmented on account of low awareness, variable clinical practices, a lack of access to genetic services, and ethical and psychosocial barriers. The objective of this study is to formulate a structured and actionable pathway for the implementation of screening for hereditary breast cancer in India. The study employed a mixed-methods study design that enabled the combination of findings from quantitative data obtained from a survey and in-depth perspectives gleaned from experts in this subject matter domain. The data analysis involved statistical testing for relationship outcomes in awareness, communication from physicians, fear barriers, and screening uptake. Case studies from international concepts helped shape a best practice approach. From the results, there is clinical evidence supporting hereditary screening, especially for high-risk individuals; however, its uptake is very low among patients. The factors that significantly influenced patients to undergo hereditary screening include recommendations by physicians, fear of results, cost limitations, lack of standardized guidelines, and lack of infrastructure to provide psychological support to patients. Misuse of genetic information is a major ethical issue restricting its acceptance. The study concludes that hereditary breast cancer screening in India can be substantially improved through a structured implementation pathway integrating physician-led awareness, standardized referral protocols, expanded access to genetic counseling, and robust ethical safeguards. The proposed pathway provides practical guidance for healthcare providers, policymakers, and insurers, positioning hereditary breast cancer screening as a scalable and impactful preventive strategy aligned with precision medicine and public health equity objectives.